Legal Construction that Strengthens Individual Legal Responsibility in Corporate Leadership Regarding Practices Social and Environmental Responsibility in Indonesia - Nur Arifudin; Purwanti Purwanti (Faculty of Law, Universitas Pekalongan, 2023)
In the realm of corporate leadership, the integration of Tanggung Jawab Sosial dan Lingkungan (TJSL) practices has gained increasing attention as organizations seek to align their operations with sustainable development goals. This paper delves into the legal constructs aimed at strengthening individual legal accountability within corporate leadership concerning TJSL practices. The study engages in a comprehensive analysis of the evolving legal landscape, highlighting mechanisms designed to foster responsible decision-making and governance within corporations. A focal point of the investigation is the examination of legal frameworks that establish a direct connection between individual executives and their fiduciary duties towards social and environmental considerations. The paper explores various jurisdictional approaches to holding corporate leaders accountable, ranging from fiduciary duties extensions to the incorporation of TJSL principles into directorial responsibilities. By scrutinizing case law, statutory provisions, and international standards, the research uncovers patterns in legal precedents that uphold the principle of individual accountability. Furthermore, the paper scrutinizes the challenges inherent in enforcing such legal constructs, especially in transnational contexts. It addresses issues of jurisdictional reach, cross-border liability, and the harmonization of diverse legal frameworks to ensure cohesive accountability standards. The study also assesses the role of corporate governance mechanisms, internal policies, and external incentives that interact with legal provisions to motivate proactive TJSL practices. In conclusion, this paper sheds light on the transformative potential of legal mechanisms in fostering a culture of responsible corporate leadership aligned with social and environmental values. It emphasizes the synergy between legal mandates and ethical imperatives, ultimately contributing to the advancement of sustainable business practices within a global context.